2007
DOI: 10.1038/nn2007
|View full text |Cite
|
Sign up to set email alerts
|

The neural correlates of subjective value during intertemporal choice

Abstract: Neuroimaging studies of decision-making have generally related neural activity to objective measures (such as reward magnitude, probability or delay), despite choice preferences being subjective. However, economic theories posit that decision-makers behave as though different options have different subjective values. Here we use functional magnetic resonance imaging to show that neural activity in several brain regions--particularly the ventral striatum, medial prefrontal cortex and posterior cingulate cortex-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

152
1,670
22
16

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,739 publications
(1,860 citation statements)
references
References 44 publications
152
1,670
22
16
Order By: Relevance
“…The thalamus serves as a critical relay structure between cortical and subcortical regions, facilitating information integration among the SN/VTA and striatum as well as prefrontal areas such as the vmPFC and dlPFC (Haber and Knutson, 2009). The vmPFC has been widely implicated in subjective value encoding Kable and Glimcher, 2007;Levy and Glimcher, 2012;Montague and Berns, 2002;Padoa-Schioppa and Assad, 2006;Plassmann et al, 2007) and has been shown to integrate value information during multi-attribute decision-making (Basten et al, 2010;Hare et al, 2011;Kahnt et al, 2011). Building on these findings, we here show that vmPFC encodes integrated cue values.…”
Section: Discussionsupporting
confidence: 65%
“…The thalamus serves as a critical relay structure between cortical and subcortical regions, facilitating information integration among the SN/VTA and striatum as well as prefrontal areas such as the vmPFC and dlPFC (Haber and Knutson, 2009). The vmPFC has been widely implicated in subjective value encoding Kable and Glimcher, 2007;Levy and Glimcher, 2012;Montague and Berns, 2002;Padoa-Schioppa and Assad, 2006;Plassmann et al, 2007) and has been shown to integrate value information during multi-attribute decision-making (Basten et al, 2010;Hare et al, 2011;Kahnt et al, 2011). Building on these findings, we here show that vmPFC encodes integrated cue values.…”
Section: Discussionsupporting
confidence: 65%
“…(a) Aversive stimuli, whether decision options that involve increased risk or punishments themselves, have frequently been shown to activate insular cortex (INS) 33,52,53,58 and ventrolateral prefrontal cortex (vlPFC) 61 . (b) Unexpected rewards modulate activation of the striatum (STR) 43,46,53,59,76 , particularly its ventral aspect, as well as the medial prefrontal cortex (mPFC) 43,53,61,76 . (c) Executive control processes required for evaluation of uncertain choice options are supported by dorsolateral prefrontal cortex (dlPFC) 52,58 and posterior parietal cortex (PPC) 33,34 .…”
Section: Resultsmentioning
confidence: 99%
“…Based on anatomy, CGp is well situated to translate subjective valuation signals into choice because it makes connections with brain areas implicated in processing reward, attention and action 74 . Moreover, this area is activated during decision making when rewards are uncertain in either amount 75 or time 76 , and the magnitude of activation depends on the subjective appeal of proffered rewards 77 . Finally, neurophysiology shows that CGp neurons respond to salient visual stimuli 78 , after visual orienting movements 78,79 and after rewards 80 , and that all these responses scale with reward size and predictability 80 .…”
Section: Neuronal Correlates Of Outcome Uncertainty and Risky Decisiomentioning
confidence: 99%
“…25 Animal and human studies have shown the relevance of this cortex in representing subjective value, particularly in relation to rewards, 26 and in error signalling after the omission of an expected reward. 27 The posterior cingulate typically responds to prediction error in conjunction with the ventromedial prefrontal cortex. 27 In previous studies, structural posterior cingulate cortex abnormalities were seen in children with callous unemotional traits 28 and some adults with psychopathy, 29 but these were not seen in the sample in this study.…”
Section: Discussionmentioning
confidence: 99%